Persia and the Classical World (The Biblical archaeology review, 2022)
For more than a millennium, from around 550 B.C.E. to 650 C.E., ancient Greece and later also Rome had a tumultuous relationship with their neighbors to the east: the Medes, Persians, Parthians, and Sasanians of ancient Iran. Although they were sometimes at peace or even united against common enemies, more often than not these […]